Sistem Pendukung Keputusan menggunakan Metode Topsis untuk Seleksi Guru Terbaik - Fransiska, Rani; Siagian , Yessica; Rohminatin, Rohminatin (Universitas Hamzanwadi, 2024)
The process of selecting the best teachers is an important aspect of ensuring optimal quality of education in a school. However, the selection process for the best teachers at SMPN 5 Kisaran often faces obstacles such as subjectivity, lack of efficiency, and lack of transparency. This research aims to produce a decision support system using the TOPSIS method to increase objectivity and effectiveness in the teacher selection process, as well as contribute to improving the quality of education. This research is a development type using waterfall, including analysis, design, coding, testing, and implementation stages. The analysis stage is to identify system requirements, the design stage is to determine the system interface, the coding stage is to build the system, and the testing stage is to validate its functionality using a black box. Teacher performance data was collected through interviews, observation, and documentation studies. Teacher performance data will be analyzed using the TOPSIS method, which involves stages of weighting criteria, calculating relative scores, and ranking teachers based on the highest scores. The results of our findings are in the form of a decision support system application for selecting the best teachers. The test results show that this system is running well and by the design and model that has been planned. With this system, it can help SMPN 5 Kisaran in selecting the best teachers.